1999
DOI: 10.1002/(sici)1097-4687(199903)239:3<255::aid-jmor3>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry, histochemistry, and innervation of cervical shoulder muscles in the cat

Abstract: Morphometric and histochemical methods were used to estimate the force‐developing capabilities and fiber‐type contents of four muscle complexes (rhomboideus, levator scapulae, trapezius, and sternomastoideus) that link the shoulder girdle to the skull and cervical vertebrae. Each complex contained at least two member muscles that were distinctive architecturally and often had specialized innervation patterns. Trapezius and sternocleidomastoideus were innervated by both cranial nerve XI and cervical spinal nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 51 publications
2
13
0
Order By: Relevance
“…The results of this study on the course, branches and distribution of the accessory nerves in the goitred gazelle and Tuj sheep were similar to those of other species in reports that mentioned the presence of both the cranial and spinal origins of the accessory nerve (Miller, 1964;Holomanova et al, 1972Holomanova et al, , 1984Pospieszny, 1984, Richmond et al, 1999.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of this study on the course, branches and distribution of the accessory nerves in the goitred gazelle and Tuj sheep were similar to those of other species in reports that mentioned the presence of both the cranial and spinal origins of the accessory nerve (Miller, 1964;Holomanova et al, 1972Holomanova et al, , 1984Pospieszny, 1984, Richmond et al, 1999.…”
Section: Discussionsupporting
confidence: 90%
“…The findings in both species studied here clearly indicated that both the spinal and cranial roots of the accessory nerve are present and prominent. Although the numbers of the spinal and cranial roots differ slightly, not only in the same animal but also between the species observed, the origin, course, branches and distribution of the accessory nerve are largely in accordance with what has been reported in the literature (Miller, 1964;Holomanova et al, 1972Holomanova et al, , 1984Pospieszny, 1984;Richmond et al, 1999), except for some mammals, including camel, giraffe and lama, that possess no spinal roots (Lesbre, 1903;Kanan, 1969;Cui-Sheng and Xie, 1998). The results are thought to be of some significance since the two models used in this study were very different and represented rare animals, even though they were mostly in line with previous literature reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, specimens were dissected immediately following euthanasia, as opposed to dissection of embalmed cadavers, and thus the entire dissection process was completed within 5–7 h from the time of death; as a result rigor mortis had only a minor effect on fascicle length measurements. Another advantage of fresh cadaver dissection was the fact that all muscles comprising the canine neck could be studied, including those which adhere closely to the vertebrae and were consequently ignored in previous studies (Kamibayashi & Richmond, 1998; Richmond et al. 1999, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…This was due to the fact that these muscles were architecturally complex and closely adhered to the vertebrae. Other researchers have faced similar problems, and have stated that these muscles are so complex that they defy analysis by dissection (Kamibayashi & Richmond, 1998; Richmond et al. 1999, 2001).…”
Section: Discussionmentioning
confidence: 99%